2012
DOI: 10.1002/rcm.5341
|View full text |Cite
|
Sign up to set email alerts
|

The gas‐phase ligand exchange reactions of cobalt and zinc acetylacetonate, hexafluoroacetylacetonate, and trifluorotrimethylacetylacetonate complexes

Abstract: The gas-phase ligand exchange reactions between Co(II) and Zn(II) complexes containing the acetylacetonate (acac), hexafluoroacetylacetonate (hfac), and trifluorotrimethylacetylacetonate (tftm) ligands were investigated using a triple quadrupole mass spectrometer. The gas-phase mixed ligand products of [Cu(acac)(tftm)](+), [Ni(acac)(tftm)](+), [Cu(hfac)(tftm)](+), and [Ni(hfac)(tftm)](+) were formed following the co-sublimation of either homo-metal or hetero-metal precursors and are reported herein for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…7(d) suggests the presence of Co(hfac)Cl 2 fragment. This fragment is not present in the mass spectrum of Co(hfac) 2 , 23 meaning that other Co-containing species must be responsible for the process of ALE of this material. Finally, it is worth mentioning that the presence of such species as Co(hfac)Cl 2 implies that at least part of the cobalt removal occurs via the formation of Co 3+ species consistent FIG.…”
Section: Thermal Desorption Investigationsmentioning
confidence: 95%
“…7(d) suggests the presence of Co(hfac)Cl 2 fragment. This fragment is not present in the mass spectrum of Co(hfac) 2 , 23 meaning that other Co-containing species must be responsible for the process of ALE of this material. Finally, it is worth mentioning that the presence of such species as Co(hfac)Cl 2 implies that at least part of the cobalt removal occurs via the formation of Co 3+ species consistent FIG.…”
Section: Thermal Desorption Investigationsmentioning
confidence: 95%
“…Previous studies demonstrated no significant product intensities at masses above m/z 650. [16][17][18] Source pressures were maintained at 10 À6 Torr, while the source and manifold temperatures were held at 160°C and 80°C, respectively. The temperature ramp on the direct exposure probe was increased from ambient temperature to 800°C over 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…[8,9] Metal beta-diketonates have been studied for decades and more recently have been reported to undergo ligand exchange in the gas phase. [10][11][12][13][14][15][16][17][18][19] During co-sublimation experiments, both partial and complete ligand exchange has been observed to occur for several species whose metal center and ligand identity have varied. To further establish the propensity of these species to undergo ligand exchange and to elucidate the mechanism associated with the prevalent ligand exchange processes of several metal beta-diketonates, the collision cell of a triple quadrupole mass spectrometer has been employed to shed light on the possible reaction pathways.…”
mentioning
confidence: 99%